Black soldier fly larvae used for environmental enrichment purposes: Can they affect the growth, slaughter performance, and blood chemistry of medium-growing chickens? - Bongiorno, Valentina; Gariglio, Marta; Zambotto, Valeria; Cappone, Eleonora Erika; Biasato, Ilaria; Renna, Manuela; Forte, Claudio; Coudron, Carl; Bergagna, Stefania; Gai, Francesco; Schiavone, Achille (Frontiers in Veterinary Science, 2022)
This research has been aimed at evaluating the effects of live black soldier fly larvae (BSFL) (Hermetia illucens) on the growth, slaughtering performance, and blood parameters of medium- growing chickens. A total of 240, 28-day-old, Label Rouge Naked Neck chickens were allotted to 4 experimental groups, according to the gender (males-females) and to the absence (control group, C) or presence (larvae group, L) of a dietary supplementation with 10% live BSFL, on the basis of the expected average daily feed intake (ADFI) (6 replicates/diet, 10 chickens/replicate). The birds were weighed weekly, and the feed consumption was recorded to calculate the average live weight, feed conversion ratio (FCR), average daily gain (ADG), and the ADFI. At 82 days of age, 2 birds/replicate (12 birds/diet) were selected and slaughtered. The blood samples were collected, and the carcass traits (carcass, breast, thigh, and organ weights and yields) were assessed. Overall, the administered live BSFL did not impair the growth and slaughtering performance, or the blood traits, while the C females showed a better FCR than the treated ones (P<0.05). The live BSFL consumption time was longer for the females than for the males (P<0.001). The weight of the immune organs (spleen and bursa of Fabricius) increased as the live BSFL supplementation increased (P<0.05). Furthermore, the provision of live BSFL reduced the gamma glutamyl transferase (GGT, U/l) activity content in the blood (P<0.05). Finally, both the leukocytes (%) and the monocytes (%) were more abundant in the C groups than in the larvae ones (P<0.05 and P<0.01, respectively). In short, the supplementation of live BSFL can be used successfully as an environmental enrichment, without affecting the growth performance of male birds. Furthermore, the immune organ activity could be enhanced by the provision of live BSFL.